Incidence of Alfvenic SC Pulse Onto the Conjugate Ionospheres. Issue 2 (3rd February 2020) - Pilipenko, Vyacheslav A.; Fedorov, Evgeniy N.; Xu, Zhonghua; Hartinger, Michael D.; Engebretson, Mark J.; Edwards, Thom R.
Abstract: A circuit analogy for magnetosphere‐ionosphere current systems has two extremes: the voltage generator (when the ground magnetic response is proportional to the ionospheric conductance) and the current generator (when the ground magnetic response practically does not depend on the ionospheric conductance). Nonsteady field‐aligned currents interact with the ionosphere in a different way depending on the ratio between the driver time scale τ and the Alfven field line eigenperiod T A . Sudden Commencement (SC) impulses at high latitudes correspond to the situation when τ ≪ T A . This case of Alfven pulses propagating independently away from the equatorial plane is analytically examined with the magnetospheric plasma box model with thin asymmetric conjugate ionospheres. At high latitudes the amplitude ratio in conjugate ionospheres in general does not correspond directly to either the current or voltage regimes. Theoretical predictions are supported by examples of typical SC event observations at conjugate magnetometer sites in Greenland and Antarctica during summer and winter periods. Key Points: Interhemispheric properties of Alfvenic pulses with duration less than field line eigenperiod must differ from larger period disturbances At high latitudes the amplitude ratio in conjugate ionospheres in general does not correspond directly to either current or voltage regimes Interhemispheric asymmetry of SC amplitudes at Greenland and Antarctica magnetometers corresponds qualitatively to the Alfvenic pulse model